Gender Inequality, Maternal Violent Injury, and Child's Mental Health in Immigrant Families - Andrei, Sorina; Hass, Barbara; Brown, Hilary; Wang, Xuesong; Fazio, Marissa; Matai, Lavina; Hadipour-Lakmehsari, Sina; Maclagan, Laura; Urquia, Marcelo; Saunders, Natasha (International Journal of Population Data Science, 2026)
Background When mothers experience assault, their children’s mental health may be impacted. We hypothesized that for children in immigrant families, the mental health impact of a mother’s assault may be exacerbated by a history of gender inequality in the mother’s birth country. Methods This population-based cohort study included children (age<18) born in Ontario, Canada, 2002–2020, and their immigrant mothers. Children were categorized on two maternal exposures: assault and birth country Gender Inequality Index. The primary outcome was five-year risk of new/worsening child mental illness, evaluated as adjusted relative risks (aRR) using modified Poisson models controlling for baseline social and health characteristics. Adjusted relative excess risk due to interaction (aRERI) assessed the joint effects of both exposures. Results We identified 90,251 children with neither maternal exposure, 246,485 exposed to maternal gender inequality only, 1,166 exposed to maternal assault only, and 4,723 with both. Compared to children with neither exposure, those exposed to both maternal outcomes had a higher five-year risk of mental illness (13.5% vs. 8.9%; aRR 1.36, 95%CI 1.26–1.48), as did those exposed to maternal violent injury only (14.7%; aRR 1.45, 95%CI 1.26–1.68), but not high gender inequality only (8.6%; aRR 0.98, 95%CI 0.95–1.00). Having both exposures produced a negative interaction for child mental illness (aRERI -0.07, 95%CI -0.20–0.05). Conclusion While children whose immigrant mothers experienced violence or originated from a high-gender inequality country conferred a high risk of mental illness, the combination of these factors did not contribute to excess mental illness risk.